DEVELOPMENT OF RISKMANAGEMENT SYSTEM IN  CONSTRUCTION PROJECTS USING SIMULATION - nan, nan; nan, nan (Iraqi Journal of Civil Engineering, 2008)
ی This research aims to highlight the role of risks management in presenting a formalapproach to entry decisions to the markets of construction through the adoption of theanalytical hierarchy techniques, and simulation, as a technique in selecting particularrisk responses.To attain the aim of the research, special data which deal with the topic of risksmanagement, and their techniques, were collected from personal interviews ofspecialists of designers and executives of construction projects.The results of data analysis of samples have shown that risks of fluctuation of supplyand demand on materials, equipment or labor and changes in government policy are the most emerged risks with respect to qualitative assessment and the most highlight risksof relative importance are risks of changes in government policy and the fluctuation ofsupply and demand on materials and internal factors. And risk responses which arerepresented by contingency and specifying a clause in the contract which is concernedwith the changeable circumstances have gained the largest share of importance ascompared with other alternatives.In the light of what have been reached by the surrounded risks of the constructionproject, a management system has been constructed which can be adopted in qualitativeassessment of risks and in simulating this assessment ,so that can be depended on inquantitative assessment of risks through quantifying the influence of risks on projectcost by using simulation technique. To gain from the advantages of computer, acomputer program has been designed that depends on the bases of the managementsystems which have been suggested to be constructed.